Strategi Campaign “Smiling West Java” dalam Meningkatkan Pariwisata Kebudayaan dan Ekonomi Kreatif - Bagas Hagy Prasetio; DADAN MULYANA (Bandung Conference Series: Public Relations, 2022)
Abstract. One of the Government Offices in Indonesia, namely the West Java Province Tourism and Culture Office, in December 2019 held a "Smiling West Java" campaign. The purpose of the campaign is to increase and attract visitors from outside the province of West Java and abroad to come. Through this research, it can be seen how the campaigns used by an institution to achieve its organizational goals. Research objectives to know the campaign strategy “Smiling West Java” in cultural and economic creative promote tourism.To know a occurring on strategic campaign “Smiling West Java” in cultural and economic creative promote tourism.To see if of tourism and culture west java created this campaign strategy “Smiling West Java”. The research uses a qualitative methodology approach case study robert k .Yin type 1 cases one analysis .The technique of using interviews data, observation, documentation and the study of literature. This research has two main subject speakers from department which handle and has made the campaign “Smiling West Java” promote tourism in culture and creative economy. The theory used grand strategy (Botan & Hazelton). Drawing conclusions: strategy campaign “Smiling West Java” in promote tourism culture and creative economy as a form of efforts to create, brending and rebuilding brand awareness the community in west java. tourist destination. Disparbud Jabar strategy created with the aim of enhancing back and revive tourism destination in west java covid-19 had a decline in visitors to the tourism in West Java. Abstrak. Salah satu Dinas Pemerintahan di Indonesia yaitu Dinas Pariwisata dan Kebudayaan Provinsi Jawa Barat pada bulan Desember 2019 mengadakan kampanye “Smiling West Java.” Tujuan dari kampanye tersebut diadakan adalah untuk meningkatkan dan menarik pengunjung luar provinsi Jawa Barat maupun mancanegara untuk datang. Tujuan penelitian untuk mengetahui bentuk strategi campaign “Smiling West Java” dalam meningkatkan pariwisata kebudayaan dan ekonomi kreatif. Untuk mengetahui hambatan yang terjadi pada strategi campaign “Smiling West Java” dalam meningkatkan pariwisata kebudayaan dan ekonomi kreatif. Untuk mengetahui mengapa dinas pariwisata dan kebudayaan provinsi Jawa Barat (Disparbud) menciptakan strategi campaign “Smiling West Java”. Penelitian menggunakan metode kualitatif pendekatan studi kasus Robert K. Yin tipe 1 satu kasus satu analisis. Teknik pengambilan data berupa menggunakan wawancara, observasi, dokumentasi dan studi kepustakaan. Penelitian ini memiliki subjek utama dua narasumber dari Disparbud yang bertanggungjawab dan berperan menciptakan strategi campaign “Smiling West Java” dalam meningkatkan pariwisata kebudayaan dan ekonomi kreatif. Teori yang digunakan grand strategy (Botan & Hazelton). Simpulan: strategi campaign “Smiling West Java” dalam meningkatkan pariwisata kebudayaan dan ekonomi kreatif sebagai bentuk upaya menciptakan brending, serta membangun kembali brand awareness masyarakat pada destinasi wisata Jawa Barat. Pihak Disparbud Jabar menciptakan strategi dengan tujuan meningkatkan kembali serta menghidupkan kembali destinasi wisata daerah Jawa Barat yang selama covid-19 sempat adanya penurunan pengunjung ke tempat wisata yang ada di Jabar